Stability Constant of Pr(III), Nd(III) and Sm(III) Chelates with Some Substituted Pyrazolines - Meshram, Y.K.; Narwade, M.L.; Mandakmare, A.M. (Asian Journal of Chemistry, 2010)
The interaction of Pr(III), Nd(III) and Sm(III) metal ions with 3(2-hydroxy-3-iodo-5-methyl-phenyl)-1,5-diphenyl-pyrazoline (ligand 1); 3(2-hydroxy-3-bromo-5-methyl-phenyl)-1-phenyl-5-( 4- methoxy-phenyl)-pyrazoline (ligand 2) and 3(2-hydroxyc3-chloro- 5-methyl-phenyl)-5-(4-methoxy-phenyl)-pyrazoline (ligand 3) have been investigated by pH-metric technique at 0.1 M ionic strength at 27 ± 0.1 °C in 70% alcohol (methanol)-water mixture. The data obtained were used to estimate the values of proton-ligand stability constant (pk) and metal-ligand stability constants (log K). It is observed that Pr(III), Nd(III) and Sm(III) metal ions formed 1 : 1 and 1 : 2 complexes with all the ligands.